A review on the modeling of fission chambers - Lyric, Zoairia (Kansas State University, 2017)
Fission chambers are ideal neutron flux surveillance instruments to ensure nuclear reactor control and safety. They can provide online, in-core, real-time measurements covering the dynamic range of neutron flux including pulse, Campbell, and current mode over decades of reactor operation cycles. The first patented fission chamber was developed by Baer et al. in 1957. It was a cylindrical assembly thermal fission counter having sensitivity of 0.7 count/neutron cm⁻² for a background measurement of 5 counts/second with ability to operate at a temperature range of 20-80 ºC [3]. Since then, fission chamber technology was developed to come up with miniature and sub-miniature dimensions withstanding high irradiation and high temperature environment making them suitable for in-core online diagnosis. Since the introduction of high temperature fission chamber technology starting in the 1970’s, the need of the advancement in modeling of the fission chambers to improve their performance has become important. The development of modeling depends upon the understanding and consideration of underlying physics of these detectors. The validation of modeling of fission chambers will need the quantification of uncertainty introduced at every stage from neutron-deposit interaction to signal shaping. Based on this objective, a detailed review was performed on fission chamber modeling and simulation covering neutron flux self-shielding, fissile deposit evolution, fission product emission, auto-absorption, electron-ion pair creation, charge recombination and avalanche, space charge effect, charge transport, propagation of electronic pulse and pulse shaping. The analytical methods, algorithmic treatments, simulation, and computation codes used so far in case of modeling different aspects of fission chambers were reviewed. Along with the numerical methods and computer codes for simulating electron drift and charge transport for the usual gas chamber detectors, the use of several fissile material evolution techniques and computation codes were observed in case of fission chamber modeling. The use higher order statistics to handle fluctuation mode and to treat noisy data were observed. In recent years, fission chamber modeling made reasonable improvement in detail physics modeling. Several analytical methods like advanced statistics for Campbellng mode and electric field distortion due to space charge effect need to be incorporated in computation codes. More progress in the areas of evolution of gas behavior, consideration of Penning, recombination, and avalanche effect still needed.
Keywords: Fission chamber modeling; Neutron monitoring; Campbell; Miniature; Fissile deposite evolution; Space charge